Great power clashes along the maritime silk road: lessons from history to shape current strategy - Rhode, Grant F. (Annapolis, Maryland: Naval Institute Press, 2023)
"Current concerns in maritime Eurasia are centered on rising powers China and India. By way of background to understanding the current regional great power rivalry within maritime Eurasia, this book asks what we can learn from historic Eurasian maritime geopolitical players and their interactions that will inform and enlighten today's international relations practitioners. Great Power Clashes along the Maritime Silk Road examines three seminal historical cases of maritime clashes in the China Seas, four in the Indian Ocean, and one in the eastern Mediterranean Sea. Each of these is an example of local or regional conflict reflecting the circumstances of time and place. The cases have been chosen to provide a comparative framework of significant premodern maritime clashes distributed along the full Eurasian maritime perimeter. Lessons include understanding struggles between continental and maritime powers in Eurasia, and understanding the decisive impact that naval leadership, intelligence, technology, alliances, and identity have had in the past and will have on the future"--
Great Power Clashes along the Maritime Silk Road : Cases and Modes of Explanation -- Chola Maritime Expansion to the Ganges, Sri Lanka, and Srivijaya : Rajendra Chola, Eleventh Century -- Limits on Mongol Maritime Expansion to Japan, Vietnam, and Java : Tran Hung Dao, Thirteenth Century -- Early Ming Voyages to the Western Ocean : Zheng He, Fifteenth Century -- Kunjali Marakkar Naval Resistance to the Portuguese on the Malabar Coast : Kunjali Marakkar, Sixteenth Century -- Limits on the Ottoman Navy in the Mediterranean Sea : Hayreddin Barbarossa, Sixteenth Century -- Japan's Thwarted Maritime Invasions of Korea : Yi Sun-sin, Sixteenth Century -- Ming Expulsion of the Dutch from Taiwan : Koxinga, Seventeenth Century -- Maratha Naval Resistance to the British on the Konkan Coast : Kanhoji Angre, Eighteenth Century -- Lessons from Eurasian Maritime History : Looking Back to Lean Forward.
Includes bibliographical references (pages 313-326) and index.
Keywords: Naval battles -- Eurasia -- History; Sea-power -- Eurasia -- History; Geopolitics -- Eurasia -- History; Balance of power; HISTORY / Asia / General; HISTORY / Military / Strategy; Eurasia -- History, Naval; Eurasia -- Foreign relations